Speech at the World Bank Group Annual Meetings Plenary - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group, discussed the following topics: new structure of global practices; Swachh Bharat Rural Sanitation Project in India, which applied knowledge of good service delivery; creation of pandemic emergency financing facility; recently announced global concessional financing facility, a new effort to address refugee crises by providing concessional development financing for middle-income countries; and working towards ending poverty and boost shared prosperity.